The Implementation of Compensation for the Rest of the Land in Land Procurement for the Construction of Public Facilities - Uslifatul Jannah; Sri Endah Wahyuningsih (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to find out and analyze the implementation of compensation for the remaining land parcels in land acquisition for the construction of public facilities in Bogor Regency, as well as to find out and analyze the obstacles and solutions in the implementation of compensation for the remaining land parcels in land acquisition for the construction of public facilities in the Regency. Bogor. This research method uses a sociological juridical approach, namely legal research that uses secondary data as initial data, which is then followed by primary data in the field or on the community. Based on the results of the study concluded: 1) The implementation of compensation for the remaining land parcels in land acquisition for the construction of public facilities in Bogor Regency, namely the implementation of the construction of the Bogor Outer Ring Road (BORR) as a whole has not been carried out optimally because there is still land that has not been paid for with various kinds of problems. . Until the end of this research, there are still 36 (thirty six) of the 171 (one hundred and seventy one) remaining land parcels that have not received compensation, namely the remaining land parcels located in Cibadak Village and Kayu Manis Village; 2) Implementation of compensation for the remaining land there are several obstacles that hinder the implementation, namely obstacles from the community which include objections to the amount of compensation, objections to the provisions on the area of the remaining land parcels to be compensated, and the application for compensation for the remaining land which is not done collectively. Meanwhile, the obstacle from the government is that there is a legal vacuum regarding the compensation mechanism for the remaining land which has an area of more than 100 m2.